2022
DOI: 10.3390/antiox11020349
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Selenium Alleviated Mouse Liver Oxidative Stress and NAFLD Induced by Obesity by Regulating the KEAP1/NRF2 Pathway

Abstract: Nonalcoholic fatty liver disease (NAFLD) occurs when excess fat is stored in the liver and it is strongly linked with metabolic syndrome and oxidative stress. Selenium (Se) is an essential micronutrient in animals, which has a variety of biological functions, including antioxidant and anti-inflammatory. However, the exact effect of dietary selenium on NAFLD and the underlying molecular mechanism are not yet clear. Herein, we fed a high-fat diet (HFD) to C57BL/6 mice to construct an in vivo NAFLD model, treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…In STZ-induced diabetic rats, dietary supplemented with inorganic selenium for 24 weeks significantly lowered serum glucose concentration ( Becker et al, 1996 ). Additionally, dietary selenium improved glucose intolerance in high-fat diet-fed mice ( Wang et al, 2022 ). However, diabetic rats also showed resistance to selenium, as sodium selenite only decreased glucose concentration for the first two weeks, while they had no further effects for the last four weeks of the experiment ( McNeill et al, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…In STZ-induced diabetic rats, dietary supplemented with inorganic selenium for 24 weeks significantly lowered serum glucose concentration ( Becker et al, 1996 ). Additionally, dietary selenium improved glucose intolerance in high-fat diet-fed mice ( Wang et al, 2022 ). However, diabetic rats also showed resistance to selenium, as sodium selenite only decreased glucose concentration for the first two weeks, while they had no further effects for the last four weeks of the experiment ( McNeill et al, 1991 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sep-1 and Sep-2 promoted Nrf2 protein expression and elevated GSH-Px activity and GSH content better than Pep-1 and Pep-2. Wang et al reported that selenium can activate the Nrf2-Keap1 pathway and protect hepatocytes from oxidative stress; 41 and Yi et al demonstrated that soybean peptides can alleviate H 2 O 2 -induced oxidative stress by activating the Nrf2-Keap1 signaling pathway and increasing the activities of intracellular antioxidant enzymes. 40 Our results suggest that selenium and soybean peptides show synergistic effects in activating the Nrf2-Keap1 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, Selenium was recognized as antioxidants to attenuate the development of NAFLD [ 43 ]. Yang Yi [ 44 ] and Seyedeh [ 45 ] et al. found high selenium exposure decreased liver steatosis, HOMA-IR, LDL/HDL-c and TC/HDL-c ratios which were aetiologies of NAFLD in NAFLD rodent models via directly suppling high-fat diets (HBD) with added selenomethionine.…”
Section: Discussionmentioning
confidence: 99%